2009
DOI: 10.1088/1367-2630/11/11/113053
|View full text |Cite
|
Sign up to set email alerts
|

Reducing quantum control for spin–spin entanglement distribution

Abstract: We present a protocol that sets maximum stationary entanglement between remote spins through scattering of mobile mediators without initialization, post-selection or feedback of the mediators' state. No time-resolved tuning is needed and, counterintuitively, the protocol generates two-qubit singlet states even when classical mediators are used. The mechanism responsible for such effect is resilient against non-optimal coupling strengths and dephasing affecting the spins. The scheme uses itinerant particles and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(60 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…Similar conclusions can be drawn for higher-s particles [5,6]. The scheme enjoys many interesting features, such as robustness against static disorder, imperfect arrangements of RCs and phase noise [6,18].…”
supporting
confidence: 74%
See 4 more Smart Citations
“…Similar conclusions can be drawn for higher-s particles [5,6]. The scheme enjoys many interesting features, such as robustness against static disorder, imperfect arrangements of RCs and phase noise [6,18].…”
supporting
confidence: 74%
“…In Refs. [6,14] it was shown that, under such working conditions, the dynamics takes place as if the static particles all occupy the same site, i.e., …”
mentioning
confidence: 99%
See 3 more Smart Citations